"Face of the giant panda" and hydrocephalus. (October 2018) - Herklots, Martin W.; Tijssen, Cees C.
Highlights: The face of the giant panda is a MRI sign in Wilson's disease. Non-pathological age-related iron accumulations is frequently seen in the red nuclei and the substantia nigra. Due to a flow void in the aqueduct in NPH patients, the MRI looks very similar to the face of the giant panda.